Studies on the effects of pericarp pigmentation on grain development and yield of black rice - Rahman, Md Mominur; Lee, Kyung Eun; Kang, Sang Gu (The Indian Journal of Genetics and Plant Breeding, 2016)
Black rice was characterized by dark purple pericarp and much lower yield than that of white rice varieties. We investigated the factors responsible for the lower yields of black rice by conducting crosses of rice with purple pericarp mutant and white pericarp cultivars. The seed weight of black rice was lower than that of brown or white rice progeny within the crosses. The F2 segregants showed increased anthocyanin deposition with simultaneous reduction of chlorophyll in the seed pericarp. These results revealed that an unknown metabolic alteration exists in the chlorophyll synthesis due to the high level of cyanindin-3- 0-glucoside deposition in the purple pericarp rice, indicating that anthocyanin deposition in the pericarp of black rice hindered the photosynthetic rate, leading to low yield. These findings suggest that the low yield of black rice is closely related to physiological factors other than the genetic yield traits